可爱俏皮或冷艳如冰 ：论金庸武侠小说《神雕侠侣》影视与 原著中小龙女形象研究 = Study of Xiao Long Nü’s character and image in fiction and film of Louis Cha’s return of the condor heroes - 黄 馨儀 Ng, Joycelyn Xin Yi (2016)
传媒科技日新月异地不断进步，诗、画和各种文学著作都能栩栩如生地通过电子媒介呈现在大荧幕前。通过影视了解文学著作的现象极为普遍，一页页的文字已化成人们手上小小四方盒中的视觉与听觉享宴。如今是影视嘉年华的时代，影视超越文学已是备受争议的课题。许多取材于文学作品的戏剧或电影，为配合随着时代变迁的视觉和剧情需求，改编者对原著中的剧情和角色做调整，贴上“改编”的标签产生了自己的作品。本文将通过金庸的经典名著《神雕侠侣》中“小龙女”在改编影视中的形象呈现分析这些改编形象与原著的落差和促使改编的原由。 It is the era of multimedia and with the improvement in technology, numerous effects and image that were deemed impossible to appear on the television screen, can now be done easily with a click on the mouse. This has caused many producers to turn their source of plots towards literature, and bring them from fiction to film. However, there are situations where film producers used “Adaptation” as a smokescreen to create films that are off the original in large extent, so as to create a sense of “originality” and also to fit the eyes of the audience. In this study, we will be looking at the imagery and character portrait of Xiao Long Nü in Louis Cha’s The Return of the Condor Heroes from both film and literature.